Florida MarketMaker and Florida Food Connect: Using E-commerce to Enhance Seafood Marketing in Florida - Charles M. Adams; William Barker (EDIS)
While the state and many non-profit organizations provide information to the Florida seafood and aquaculture industry to help them market their catch, they offer few resources facilitating e-commerce. As a business tool, e-commerce can help expedite the buying and selling of seafood products among consumers, producers, and other businesses within the food industry value chain. E-commerce is a new promotional strategy producers can use to improve their marketing efficiency. For example, the affiliated websites Florida MarketMaker and Florida Food Connect are designed to enhance the online presence for the Florida seafood industry. Web portals such as these increase the visibility of seafood businesses by allowing dealers to create a searchable online profile attracting more customers seeking locally sourced seafood. This 6-page fact sheet was written by Charles M. Adams and William Barker, and published by the UF Department of Food and Resource Economics, May 2014.